(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
The purpose of this study was to determine the types of code-mixing, and teachers’ perception using code-mixing in the learning at SMP Kartika XX-2 Makassar. This study used descriptive qualitative research methods and data collection techniques were observation and interviews. The subject of this research was an English teachers at SMP Kartika XX-2Makassar. Based on the observation, that there were three kinds of code-blending involved by English teachers in learning, in particular intra-sentential code-blending, intra-lexical code-blending and including changes in articulation, at SMP Kartika XX-2 Makassar both of teachers used the first type of code-mixing, namely intra-sentential code-mixing in class. While the perception of teachers using code-mixing in learning is situation and lack of vocabulary.